Comparison of diametric and volumetric changes in Stanford type B aortic dissection patients in assessing aortic remodeling post-stent graft treatment - Wan Ab Naim, N.; Sun, Zhonghua; Liew, Y.M.; Chan, B.T.; Jansen, Shirley; Lei, J.; Ganesan, P.B.; Hashim, S.A.; Sridhar, G.S.; Lim, Einly (AME Publishing Company, 2021)
Background: The study aims to analyze the correlation between the maximal diameter (both axial and orthogonal) and volume changes in the true (TL) and false lumens (FL) after stent-grafting for Stanford type B aortic dissection. Method: Computed tomography angiography was performed on 13 type B aortic dissection patients before and after procedure, and at 6 and 12 months follow-up. The lumens were divided into three regions: the stented area (Region 1), distal to the stent graft to the celiac artery (Region 2), and between the celiac artery and the iliac bifurcation (Region 3). Changes in aortic morphology were quantified by the increase or decrease of diametric and volumetric percentages from baseline measurements. Results: At Region 1, the TL diameter and volume increased (pre-treatment: volume =51.4±41.9 mL, maximal axial diameter =22.4±6.8 mm, maximal orthogonal diameter =21.6±7.2 mm; follow-up: volume =130.7±69.2 mL, maximal axial diameter =40.1±8.1 mm, maximal orthogonal diameter =31.9+2.6 mm, P<0.05 for all comparisons), while FL decreased (pre-treatment: volume =129.6±150.5 mL; maximal axial diameter =43.0±15.8 mm; maximal orthogonal diameter =28.3±12.6 mm; follow-up: volume =66.6±95.0 mL, maximal axial diameter =24.5±19.9 mm, maximal orthogonal diameter =16.9±13.7, P<0.05 for all comparisons). Due to the uniformity in size throughout the vessel, high concordance was observed between diametric and volumetric measurements in the stented region with 93% and 92% between maximal axial diameter and volume for the true/false lumens, and 90% and 92% between maximal orthogonal diameter and volume for the true/false lumens. Large discrepancies were observed between the different measurement methods at regions distal to the stent graft, with up to 46% differences between maximal orthogonal diameter and volume. Conclusions: Volume measurement was shown to be a much more sensitive indicator in identifying lumen expansion/shrinkage at the distal stented region.